Feel Safe as a Means to Improve Minor s Digital Skills and Disaster Resilience - Casareale, Cristina; Gilio, Sharon; Graziani, Francesco (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
Students of today (aged 3-24 years) are immerged in a digitalized world, in which digital technology such as smartphones, tablet, the internet and social networks characterize most youngsters social interactions. Consequently, the use of technology is spreading within school contexts, although with distinct significant differences. For instance, higher education is increasingly moving towards digital-based teaching and learning practices, operationalized through digital platforms accessible through electronic devices (Piromalli and Viteritti, 2019). Conversely, the use of technological tools in primary and secondary school is still limited and schools still need to find a way to integrate digital literacy into their curricula and foster a teaching method that offers links with the present and future life of children and adolescents (Burnett, 2009), as «they have not known the world without cell phones, computers and internet and could not imagine how things would work without these devices» (Vincze, 2015:125). Children and adolescents, indeed, live in a shaded world in which the online and offline worlds merges in an Onlife (Floridi, 2015) dimension that shapes their educational and social reality.